2016
DOI: 10.1016/j.psychres.2016.04.122
|View full text |Cite
|
Sign up to set email alerts
|

Examining affect and perfectionism in relation to eating disorder symptoms among women with anorexia nervosa

Abstract: This study examined personality and affective variables in relation to eating disorder symptoms in anorexia nervosa (AN). Women (N=118) with DSM-IV AN completed baseline questionnaires (Beck Depression Inventory, Frost Multidimensional Perfectionism Scale) and interviews (Eating Disorder Examination, Yale-Brown-Cornell Eating Disorder Scale), followed by two weeks of ecological momentary assessment (EMA) involving multiple daily reports of affective states and eating disorder behaviors. Hierarchical regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…The elevated psychopathology among the Moderate and High Maladaptive Perfectionism groups parallels prior research indicating that maladaptive characteristics of perfectionism are associated with negative outcomes in AN (Ashby et al 1998; Boone et al 2010; Bulik et al 2003; Lavender et al 2016; Slof-Op’t Landt et al 2016). In contrast, few studies have examined whether adaptive forms of perfectionism are problematic in AN.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The elevated psychopathology among the Moderate and High Maladaptive Perfectionism groups parallels prior research indicating that maladaptive characteristics of perfectionism are associated with negative outcomes in AN (Ashby et al 1998; Boone et al 2010; Bulik et al 2003; Lavender et al 2016; Slof-Op’t Landt et al 2016). In contrast, few studies have examined whether adaptive forms of perfectionism are problematic in AN.…”
Section: Discussionsupporting
confidence: 76%
“…Facets of maladaptive perfectionism (e.g., concern over mistakes and doubts about actions) have been found to differentiate individuals with eating disorders from non-clinical and psychiatric controls, while aspects of adaptive perfectionism (e.g., high personal standards) have not (Ashby et al 1998; Bulik et al 2003). Further, a recent analysis from the same dataset as used in this investigation found that a composite maladaptive perfectionism score was associated with the severity of cognitive eating disorder symptoms in AN (Lavender et al 2016). In contrast, there has been little investigation of the independent effects of adaptive components of perfectionism in AN.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…1 For example, negative affect is a risk factor for eating pathology, 32-33 and more recent research suggests that variability in affective lability and intensity may be salient to eating disorder symptoms. 34-35 …”
Section: The Roy Adaptation Modelmentioning
confidence: 99%